QRS COMPLEX DURATION AND CLINICAL FEATURES OF PATIENTS WITH PERMANENT PACEMAKERS - I. V. Shanina; D. E. Volkov; D. A. Lopin; N. I. Yabluchansky (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2013)
125 patients (57 – women, 68 – males) with permanent pacing were examined. Among the indications for pacemaker installation there were atrio-ventricular block (AV-block) – 77 people (62 ± 4 %), sick sinus node syndrome (SSNS) – 32 patients (26 ± 4 %), bradysystolic AF – 8 patients (6 ± 2 %). 8 patients with cardioresynchronization therapy (6 ± 2 %) were also included. Average age was 69 ± 7 years. The patients were divided into two groups: first – patients with QRS complex duration under 120 mc, second – QRS duration complex with more than 120 mc. It was found that QRS complex duration with more than 120 mc is associated with males and patients with postinfarction cardiosclerosis, heavier functional class of heart failure and atrial fibrillation. Given the trend towards more clinically significant cardiovascular disease in patients with a QRS complex duration with more than 120 mc, this group of patients needs optimal therapeutic management. The results show the feasibility of and prospects for further study of this group of patients.